Mental and behavioral disorders in people with myopia - Drozdov, Vladymyr (Psychosomatic Medicine and General Practice, 2025)
The aim. The work was to determine the features of mental and behavioral disorders in myopia. Materials and methods. 200 patients with myopia were examined at the British Ophthalmological Center in Kyiv. Pathopsychological diagnostics, the "Methodology of Multilateral Personality Research", "Personal questionnaire of the Bekhterev Institute" were used. The study was conducted in accordance with the principles of the Declaration of Helsinki of the World Medical Association. Mathematical processing of the study results was performed using mathematical statistics methods. Results. Among people with myopia, affective disorders (mood disorders) were diagnosed in 20,5 % of cases: mild depressive episode (9,0 %), dysthymia (11,5 %); in 65,0 % - neurotic, stress-related and somatoform disorders: mixed anxiety-depressive disorder (11,0 %), neurasthenia (55,5 %), hypochondriac disorder (11,0 %); in 2,0 % - persistent personality changes not related to brain damage or disease: other persistent personality changes (2,0 %). Conclusions. Violation of social and psychological adaptation, due to the formation of maladaptive types of attitude towards the disease in 92,7-100,0 % of people with myopia, significantly complicated the process of their rehabilitation.